2018
DOI: 10.1080/21691401.2018.1439839
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Synthesis, characterization and in vitro evaluation of magnetic nanoparticles modified with PCL–PEG–PCL for controlled delivery of 5FU

Abstract: Magnetic nanoparticles have properties that cause to apply them in cancer therapy and vehicles for the delivery of drugs such as 5FU, especially when they are modified with biocompatible copolymers. The aim of this study is to modify superparamagnetic iron oxide nanoparticles (SPIONPs) with PCL-PEG-PCL copolymers and then utilization of these nanoparticles for encapsulation of anticancer drug 5FU. The ring-opening polymerization (ROP) was used for the synthesis of PCL-PEG-PCL copolymer by ε-caprolactone (PCL) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(21 citation statements)
references
References 46 publications
2
17
0
2
Order By: Relevance
“…Current investigations have also synthesized IONPs employing different shells with anticancer agents conventionally administered, such as β-cyclodextrin [ 135 ], carmustine [ 136 ], cetuximab [ 137 , 138 , 139 ], cytarabine [ 140 ], daunomycin [ 141 ], docetaxel [ 142 , 143 ], epirubicin [ 144 ], 5-fluorouracil [ 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 ], gemcitabine [ 22 , 154 , 155 , 156 , 157 , 158 ], methotrexate [ 159 , 160 , 161 ], mitoxantrone [ 162 , 163 , 164 , 165 ] and paclitaxel [ 27 , 104 , 166 , 167 , 168 , 169 , 170 , 171 , 172 ]. It is noteworthy, however, that these nanosystems demonstrate magnetic properties only in the presence of external magnetic fields to prevent agglomerations of nanoparticles [ 111 ] and to allow a satisfactory performance in the target sites.…”
Section: Drugs Bound To Ionpsmentioning
confidence: 99%
“…Current investigations have also synthesized IONPs employing different shells with anticancer agents conventionally administered, such as β-cyclodextrin [ 135 ], carmustine [ 136 ], cetuximab [ 137 , 138 , 139 ], cytarabine [ 140 ], daunomycin [ 141 ], docetaxel [ 142 , 143 ], epirubicin [ 144 ], 5-fluorouracil [ 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 ], gemcitabine [ 22 , 154 , 155 , 156 , 157 , 158 ], methotrexate [ 159 , 160 , 161 ], mitoxantrone [ 162 , 163 , 164 , 165 ] and paclitaxel [ 27 , 104 , 166 , 167 , 168 , 169 , 170 , 171 , 172 ]. It is noteworthy, however, that these nanosystems demonstrate magnetic properties only in the presence of external magnetic fields to prevent agglomerations of nanoparticles [ 111 ] and to allow a satisfactory performance in the target sites.…”
Section: Drugs Bound To Ionpsmentioning
confidence: 99%
“…Previous studies have reported that Chrysin possesses potent anti-inflammatory and anti-oxidant properties [29,30]. On the other hand, curcumin is a naturally occurring polyphenolic compound with a broad range of favourable biological functions, including anti-cancer, antioxidant and anti-inflammatory activities [31]. The low bioavailability and in vivo stability of curcumin, however, require the development of suitable carrier vehicles to deliver the molecule in a sustained manner at therapeutic levels.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been demonstrated that hydrophobic/hydrophilic ratio has crucial role in stabilizing of formed micelle.it has been also reported the micelles formed by triblock copolymer are more advantageous over diblock formed micelles in terms of stability which is attributed to lower critical micelle concentration (CMC) of triblock copolymers [26]. PCL-PEG-PCL is a type of PCL/PEG based triblock which has been utilized as 5-FU nanocarrier [27]. A comprehensive evaluation on PCL/PEG based triblock, consisting PCL-PEG-PCL and PEG-PCL-PEG with different ratio of coplymerization, has demonstrated that CMC values of PEG-PCL-PEG type is about half of those measured for its identical PCL-PEG-PCL which indicates higher stability of PEG-PCL-PEG type [28].…”
Section: Discussionmentioning
confidence: 99%